A review of polymeric membranes and processes for potable water reuse. (June 2018) - Warsinger, David M.; Chakraborty, Sudip; Tow, Emily W.; Plumlee, Megan H.; Bellona, Christopher; Loutatidou, Savvina; Karimi, Leila; Mikelonis, Anne M.; Achilli, Andrea; Ghassemi, Abbas; Padhye, Lokesh P.; Snyder, Shane A.; et al.
Abstract: Conventional water resources in many regions are insufficient to meet the water needs of growing populations, thus reuse is gaining acceptance as a method of water supply augmentation. Recent advancements in membrane technology have allowed for the reclamation of municipal wastewater for the production of drinking water, i.e., potable reuse. Although public perception can be a challenge, potable reuse is often the least energy-intensive method of providing additional drinking water to water stressed regions. A variety of membranes have been developed that can remove water contaminants ranging from particles and pathogens to dissolved organic compounds and salts. Typically, potable reuse treatment plants use polymeric membranes for microfiltration or ultrafiltration in conjunction with reverse osmosis and, in some cases, nanofiltration. Membrane properties, including pore size, wettability, surface charge, roughness, thermal resistance, chemical stability, permeability, thickness and mechanical strength, vary between membranes and applications. Advancements in membrane technology including new membrane materials, coatings, and manufacturing methods, as well as emerging membrane processes such as membrane bioreactors, electrodialysis, and forward osmosis have been developed to improve selectivity, energy consumption, fouling resistance, and/or capital cost. The purpose of this review is to provide a comprehensive summary of the role of polymeric membranes and process components in the treatment of wastewater to potable water quality and to highlight recent advancements and needs in separation processes. Beyond membranes themselves, this review covers the background and history of potable reuse, and commonly used potable reuse process chains, pretreatment steps, and advanced oxidation processes. Key trends in membrane technology include novel configurations, materials, and fouling prevention techniques. Challenges still facing membrane-based potable reuse applications, including chemical and biological contaminant removal, membrane fouling, and public perception, are highlighted as areas in need of further research and development.